Effect of Combined Perftoran and Indocyanine Green-Photodynamic Therapy on HypoxamiRs and OncomiRs in Lung Cancer Cells - Gamal-Eldeen, Amira M.; Alrehaili, Amani A.; Alharthi, Afaf; Raafat, Bassem M. (Frontiers in Pharmacology, 2022)
Indocyanine green (ICG) is a non-toxic registered photosensitizer used as a diagnostic tool and for ‎photodynamic therapy (PDT). Hypoxia is one the main factors affecting PDT efficacy. ‎Perfluorodecalin emulsion (Perftoran®) is a known oxygen carrier. This study investigated the effect ‎of Perftoran® on ICG/PDT efficacy in presence and absence of Perftoran® via evaluation of ‎phototoxicity by MTT; hypoxia estimation by pimonidazole, HIF-1α/β by ELISA and 17 miRNAs ‎‎(tumor suppressors, OncomiRs, and hypoxamiRs) were analyzed by qPCR. Compared to ICG/PDT, ‎Perftoran‎‎®/ICG/PDT led to higher photocytotoxicity, inhibited pimonidazole hypoxia adducts, inhibited ‎HIF-1α/β concentrations, induced in the expression of tumor suppressing miRNAs let-7b/d/f/g and ‎strongly inhibited the pro-hypoxia miRNA let-7i. Additionally, Perftoran‎‎®/ICG/PDT suppressed the ‎expression of the oncomiRs miR-155, miR-30c, and miR-181a and the hypoxamiRs miR-210 and ‎miR-21, compared to ICG/PDT. In conclusion, Perftoran® induced the phototoxicity of ICG/PDT and ‎inhibited ICG/PDT-hypoxia via suppressing HIF-α/β, miR-210, miR-21, let-7i, miR-15a, miR-30c, and ‎miR-181a and by inducing the expression of let-7d/f and miR-15b.‎